2012
DOI: 10.1021/ic202626c
|View full text |Cite
|
Sign up to set email alerts
|

New Iron(II) Spin Crossover Coordination Polymers [Fe(μ-atrz)3]X2·2H2O (X = ClO4¯, BF4¯) and [Fe(μ-atrz)(μ-pyz)(NCS)2]·4H2O with an Interesting Solvent Effect

Abstract: A potential bridging triazole-based ligand, atrz (trans-4,4'-azo-1,2,4-triazole), is chosen to serve as building sticks and incorporated with a spin crossover metal center to form a metal organic framework. Coordination polymers of iron(II) with the formula [Fe(μ-atrz)(3)]X(2)·2H(2)O (where X = ClO(4)(-) (1·2H(2)O) and BF(4)(-) (2·2H(2)O)) in a 3D framework and [Fe(μ-atrz)(μ-pyz)(NCS)(2)]·4H(2)O (3·4H(2)O) in a 2D layer structure were synthesized and structurally characterized. The magnetic measurements of 1·2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…The Se derivative displays, as expected with the increase of ligand field strength, a ST at higher temperature but with a narrower hysteresis (~6 K) [326]. A similar 2D ST grid was found for [Fe(baztrz)(pyz)(NCS) 2 ]·4H 2 O (baztrz = trans -4,4′-azo-1,2,4-triazole) with the replacement of one btr by pyrazine [327]. Using only one bridging bis-tetrazole afforded another 2D SCO grid but with a less cooperative behavior [328329].…”
Section: Reviewsupporting
confidence: 66%
“…The Se derivative displays, as expected with the increase of ligand field strength, a ST at higher temperature but with a narrower hysteresis (~6 K) [326]. A similar 2D ST grid was found for [Fe(baztrz)(pyz)(NCS) 2 ]·4H 2 O (baztrz = trans -4,4′-azo-1,2,4-triazole) with the replacement of one btr by pyrazine [327]. Using only one bridging bis-tetrazole afforded another 2D SCO grid but with a less cooperative behavior [328329].…”
Section: Reviewsupporting
confidence: 66%
“…Thus, it has been extensively shown that the spin-transition can be significantly affected by the intermolecular interactions induced by solvent molecules [14][15][16][17][18][19][20][21][22][23][24][25][26]. Solvent molecules of crystallisation can affect the transition temperature (T 1/2 ) [26][27][28][29][30][31][32][33][34][35][36], the nature of the spin-transition as well as the degree of cooperativity and thermal hysteresis that occurs [12,[37][38][39][40]. Previous studies have indicated that the elastic interactions between the SCO active metal centres can be enhanced by the formation of hydrogen-bonding networks between solvent and/or anion molecules, leading to abrupt and hysteric spin-transitions [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The spin-crossover (SCO) phenomenon in transition metal complexes is still a very promising approach for the development of bistable magnetic materials. One of the main advantages of spin-crossover complexes is the possibility to achieve a SCO with hysteresis around room temperature for future applications, whereas single-molecule magnets can only be used as molecular switches at liquid helium temperatures. , The disadvantage of SCO complexes, however, is the strong dependency of the spin state and spin transition on cooperative interactions in the solid state. ,, The intermolecular interactions in SCO complexes are most commonly mediated through hydrogen bonding and π–π interactions, with the ligand system and the anions playing an important role. , A very important factor is the crystal solvent in the SCO compound that can affect the transition temperature, the kind of SCO or even the spin state of the system. These changes can arise from divergent space groups and crystal packing or different hydrogen bonding interactions in the solid state, which influence the ligand field strength . There are different examples in the literature describing solvent effects on the spin transition temperature, hysteresis width, ,, or the spin state. The effect can, in very few cases, even be reversibly triggered by desolvation and resolvation of the solvent molecules. , …”
Section: Introductionmentioning
confidence: 99%